Black rhino conservation in Tanzania: translocation efforts and further challenges - Fyumagwa, Robert; Nyahongo, Julius (Pachyderm, 2010)
Tanzania had many black rhinos (Diceros bicornis) in the 1960s but was hit by ruthless poaching between the 1970s and late 1980s. From the 1990s, the country declared a war against unscrupulous poachers in order to conserve the few remaining rhinos. The current strategy is to reintroduce black rhinos that were originally from East Africa in order to increase genetic diversity. Three translocations of black rhinos between 1997 and 2001 involved 10 animals from South Africa, two of which were reintroduced to Ngorongoro Crater and eight to Mkomazi National Park. In 2007, two black rhinos from Port Lympne Wild Animal Park, UK, were introduced into a sanctuary adjacent to Ikorongo-Grumeti Game Reserves. In June 2009, three black rhinos from the Czech Republic were translocated to Mkomazi National Park. Another translocation operation is expected to begin in May 2010 whereby 32 black rhinos will be translocated into the Serengeti ecosystem from Thaba Tholo, Thabazimbi, South Africa. Although the first five translocation operations went well, the challenge is the management of the reintroduced rhinos amid the growing social-ecological pressures affecting protected areas. Management authorities should consider the recommended sex ratio for rhino populations to avoid excessive male aggression. Keywords: Black rhinos, conservation, poaching, translocation La Tanzanie avait beaucoup de rhinocéros noirs (Diceros bicornis) dans les années 1960 mais elle a été touchée par un braconnage impitoyable entre les années 1970 et la fin des années 1980. Depuis les années 1990, le pays fait la guerre contre les braconniers sans scrupules en vue de conserver les quelques rhinocéros qui restent. La stratégie actuelle est de réintroduire des rhinocéros noirs qui étaient originairement d’Afrique de l’Est pour amplifier la diversité génétique. Trois translocations de rhinocéros noirs entre 1997 et 2001 concernaient 10 animaux provenant d’Afrique du Sud, deux d’entre eux ont été réintroduits dans le Parc national du cratère de Ngorongoro et huit dans le Parc national de Mkomazi. En 2007, deux rhinocéros noirs provenant du Parc de la faune de Port Lympne, au Royaume-Uni ont été introduits dans le sanctuaire adjacent de la Réserve naturelle d’Ikorongo-Grumeti. En juin 2009, trois rhinocéros noirs provenant de la République tchèque ont été transférés au Parc national Mkomazi. Une autre opération de translocation par laquelle 32 rhinocéros noirs seront transférés dans l’écosystème Serengeti à partir de Thaba Tholo, Thabazimbi en Afrique du Sud est prévue de commencer en mai 2010. Bien que les cinq premières opérations de translocation se soient bien passées, le défi reste de savoir comment gérer des rhinocéros réintroduits au milieu de pressions socio-écologiques croissantes qui affectent les aires protégées. Les autorités de gestion devraient examiner la sex-ratio recommandée pour les populations de rhinocéros pour éviter une agression mâle excessive.